PENGARUH PERTUMBUHAN EKONOMI DAN JUMLAH PENDUDUK TERHADAP IPM PROVINSI SULAWESI TENGAH - Alif Gharneza; Arfida Boedirochminarni; Hendra Kusuma (Jurnal Ilmu Ekonomi JIE, 2019)
Aiming to analyse the influence of economic growth and population over the Human Development Index (HDI) in the Regency/Municipality of Central Sulawesi, this study applies Human Development Index (Y) as independent variable and Economic Growth (XI) and Population (X2) as dependent variables. This study uses time-series and cross-section of 12 regencies and 1 municipality in Central Sulawesi in the period 2008 and 2016 which have the most significant influence over HDI. The data techniques are including the regression method of Data Panel with Data Panel Estimation test, parameter significant test, and hypothesis test using software Eviews 9.0. The data is obtained from scientific journals and literature related to the topic of the study and Statistics Indonesia in Central Sulawesi Province. The result shows that the variable of economic growth has significantly negatively influenced the HDI, but the population shows positive influence and has not been significant for HDI. The regression shows that 64% of the independent variable variants explain the Economic Growth in Central Sulawesi, whereas the rest is influenced by factors non-estimation model